Characterisation, antimalarial and biological activities of secondary metabolites from leaves of anonidium mannii - Makoni, Pfungwa Gervase (Rhodes University, Faculty of Science, Department of Chemistry, 2017)
Anonidium mannii is a plant of the Annonaceae genus which is used traditionally in Africa for the treatment of gonorrhoea, malaria, cancer, skin inflammation and dysentery. In this study we will evaluate antimalarial, antifungal, anti - tuberculosis, antibacterial activities and cytotoxicity of different fractions in order to provide a scientific rationale for the traditional use of Anonidium mannii as well as provide possible novel drugs in the treatment of multi drug resistant strains of parasites and bacteria. Extracts from dried leaves were obtained by using solvent extraction and different fractions obtained using column chromatography eluted with solvents of varying polarities to obtain a wide range of metabolites. The antimalarial activity of the various fractions and some pure compounds was evaluated using plasmodium lactate dehydrogenase (pLDH) assay. Cytotoxicity was evaluated using HeLa cells while anti "“ tuberculosis assay was evaluated using the green fluorescent protein. Antibacterial activity of the extracts was evaluated using micro-dilution assay against Gram-positive (Staphylococcus aureus and Enterococcus faecalis) bacteria and Gram-negative (Escherichia coli and Salmonella typhi) bacteria. Antifungal activity was evaluated against Candida albicans. The antimalarial assays yielded some fractions with promising IC50 values. The selected fractions yielded activities ranging between 0.73 Î¼g/mL and 20.23 Î¼g/mL. The fraction with the best activity was obtained from a hexane/ethyl acetate fraction. AM1C, a cholestane, showed the best activity from the pure metabolites that were screened. AM3C, stigmasterol, a pure compound gave the best antifungal activity with an MIC of 0.063 Î¼g/mL. AM9C another pure compound (sterol) showed the best activity against S. typhi with a value of 0.031 Î¼g/mL. AM2C a pure compound showed an activity of 0.063 Î¼g/mL against E. faecalis. The best cytotoxicity was demonstrated by the fraction C2AM3P with a cell viability of 7.1 Â± 0.2 % while AM1C had a viability of 20.2 Â± 1.2 %. Several pure metabolites were isolated and four of these were positively identified as steroids. Of these steroids the structure of three novel metabolites from A. mannii was deduced. The study showed promising antibacterial, antifungal, anti "“ tuberculosis, antimalarial and anticancer activity of A. mannii. These results validate the use of A. manni against cancer, skin inflammation which is caused by fungus, malaria and bacterial diseases.
Keywords: Anonidium mannii -- Therapeutic use; Botanical chemistry; Annonaceae -- Therapeutic use; Apocynaceae -- Therapeutic use; Malaria -- Chemotherapy; Tuberculosis -- Chemotherapy; Bacterial diseases -- Chemotherapy; Cancer -- Chemotherapy